Analysis of deformation evolution characteristics of the northern Lajishan fault before the Jishishan MS6.2 earthquake based on GNSS observations - Liao, Jiayan; Ma, Haiping; Feng, Jiangang; Li, Minjuan; Zhang, Jinpeng (Frontiers in Earth Science, 2024)
A MS6.2 earthquake struck Jishishan Country in Gansu Province on 18 December 2023. The earthquake occurred on the eastern branch of the Northern Lajishan fault (NLJSF) which has never experienced such a violent seismic event in recorded history. In this study, multiple periods of GNSS campaign observation data and continuous observation data are collected to reveal the crustal deformation evolution characteristics of the eastern branch of the NLJSF before the earthquake, focusing on the dynamic behavior of the causative fault, regional strain parameter features, and the variation of GNSS baselines across the NLJSF. Velocity field data show that the differential movement on both sides of the fault zone before the earthquake accumulated energy for the occurrence of the earthquake. Cross-fault profile analyses indicate a noticeable weakening of horizontal shortening on both fault flanks, suggesting a nearing fault lockup. The baseline time series and strain parameter time series results both show that the study area is mainly NEE-trending compression deformation. In addition, before the earthquake, multiple baseline results and strain parameter time series deviated from the linear trend and gradually flattened, indicating a strain accumulation in the study area. The overall crustal deformation evolution shows a relatively high earthquake risk before the Lajishan earthquake.